Erdoğan and the Turkish opposition revisit the Kurdish question - Mesut Yeğen (Stiftung Wissenschaft und Politik (SWP), 2022)
Not long ago, the Kurdish question (KQ) topped the agenda of Turkish politics. Thanks mainly to what was called the Resolution Process between 2009 and 2015, there was a tense but lively political and public discussion on this colossal problem that the Turkish republic has long been tackling with since its foundation. In the past few years, however, the KQ ceased to be a priority issue in Turkish politics. So much so that the "terror question", a watchword for the KQ in the daily lexicon of mainstream Turkish politics, is no longer regarded by the Turkish public as being among the country's top political problems. However, recently, there have appeared some new signs which indicate that the KQ will most likely return to the political agenda. Both Turkish President Erdoğan and the leaders of the country's opposition parties have taken steps that reveal that they will revisit the KQ as the 2023 Turkish general election approaches.
Keywords: 320